Mniejszość polska w odrodzonej Łotwie - Michaliszyn, Monika (Investigationes Linguisticae, 2019)
This article concerns the least-described period in the literature on the subject of the history of Latvian Poles - the time after Latvia regained its independence. The national movement strangled after the incorporation of the Republic of Latvia into the USSR for fifty years was cultivated illegally most often in the so-called Polish houses. The nucleus of Polish organizations established with the consent of the authorities in the end of the 1970s laid the foundations of the Association of Poles in Latvia ZPŁ) on the turn of independence at the turn of 1980s. Soon, a dozen of his branches were created. The ZPŁ is actively working to cultivate Polishness and propagate Polish culture. Thanks to his activities, a Polish school network was established in Latvia. Problems included in the work are presented in the historical and cultural perspective. A large part of the information presented is the result of a record of interviews with representatives of the Polish community and the result of the use of rich online resources illustrating the dynamic process of life of contemporary Poles in Latvia.